Journey of India Meteorological Department during last 150 years (MAUSAM, 2025)
The article describes the developments that led to the establishment of the India Meteorological Department in 1875, the seminal and inspiring contributions of the pioneers and the visionaries, and IMD’s continuing progress through the last 150 years in the service of the nation.